Can Inflammatory Hematological Parameters be a Guide to Late-onset Fetal Growth Restriction? - kırmızı, Demet Aydogan; Baser, Emre; Onat, Taylan; Caltekin, Melike Demir; Kara, Mustafa; Yalvac, Ethem Serdar (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Purpose To compare the rates obtained from hematological parameters in cases of late-onset idiopathic fetal growth restriction (FGR) with healthy pregnancies and to evaluate the effect on neonatal outcomes.Methods The study group consisted of 63 pregnant women with late-onset idiopathic FGR and the control group consisted of 91 healthy pregnant women. The determined rates were calculated from the control hemograms of patients at 28 weeks. Both groups were compared for neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), and other parameters.Results NLR, leukocyte and neutrophil levels were significantly higher in the FGR group (p<0.05). There was no significant difference in PLR, platelet and lymphocyte levels between the groups (p>0.05). To predict FGR, the best cut-off value of NLR was determined to be 4.11 with 56% sensitivity and 88% specificity values.Conclusion Neutrophil, lymphocyte and platelet interactions have an important role in FGR development. Inflammation can be involved in the etiopathogenesis in late-onset FGR.
Keywords: Fetal growth restriction; inflammation; NLR; PLR; Apgar